On the one class of the glycaemia regulation models - Meilūnas, Mečislavas (Lietuvos matematikos rinkinys, 1998)
A new approach in mathematical modelling of the Diabetes mellitus in discussed. A class of mathematical models is constructed in order to describe some features of glycaemia regulation mechanisms.